Developing a Community-Based Competency Learning Model for Students in Basic Education: Developing a Community-Based Competency Learning Model for Students in Basic Education - Thepthaiamnouy, Rietthi; Chanvirat, Waradee; Jongkonklang, Sirinat (RATANABUTH JOURNAL, 2025)
This research and development study aimed to develop, implementation, and scale up a community-based competency learning management model focusing on academic achievement and learner competencies for basic education students. The sample consisted of 20 school administrators (directors, deputy directors, and academic heads), 74 teachers, and 427 students from Nakhon Ratchasima Primary Educational Service Area Office 1 during the 2022 academic year. Research instruments included record forms, interview forms, competency-based learning management model, academic achievement tests, and learner competency assessment forms. Data were analyzed using frequency, percentage, mean, standard deviation, and content analysis. The findings revealed that: 1) The competency-based learning management model comprised characteristics, objectives, community-based Sandbox curriculum development guidelines, and curriculum construction processes, resulting in a prototype classroom-level Sandbox curriculum. 2) The implementation of the competency learning management model integrated mathematics, Thai language, and social studies using significant local sites and community wisdom, fostering leadership, communication skills, creative problem-solving abilities with overall high appropriateness and consistency. 3) The scaling up of the competency-based learning management model effectively enhanced learner competencies through integrated community-based learning that developed students as community managers.